Trend of the result on Paralympic Games at swimmers with intellectual impairment - Stankovic, M.; Projovic, A.; Pejcic, A.; Kostic, S.; Dogan, O.; Kapo, A. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of the research was to determine the trend of the development of results at the POG for swimmers with II, of both sexes, and formation of a prediction model for the results of the medal winners at the following POG. Given the fact that, after 2000, there was a ban on the participation of athletes with II at the POG in 2004 and 2008, the prediction model for the results of the medal winners at the POG in Tokyo 2020 could not be developed. Therefore, a descriptive analysis of the trend in the development of the results was made. An increase in the results was observed in both competitions and in all events. The significance of this paper lies in the fact that it can provide an approximate answer to the question posed by the coaches of top-class swimmers with II: what kind of result must a male or female swimmer with II achieve in class S14 in order to win a medal at the next POG?